Northern Bobwhite Demographics and Resource Selection Are Explained by Prescribed Fire with Grazing and Woody Cover in Southwest Missouri - Frank R Thompson III; Mitch D Weegman; Emily A Sinnott; Alisha R Mosloff; Kyle R Hedges; Frank L. Loncarich; Thomas R Thompson; Nicholas C Burrell; Stasia Whitaker; David E Hoover (National Quail Symposium Proceedings, 2022)
Understanding the effects of landscape management on northern bobwhite (Colinus virginianus; hereafter, bobwhite) population growth requires information about seasonal- and stage-specific demographic parameters linked across the annual cycle. We review results to date from 3 years (2016–2018) of an intensive field study evaluating drivers of bobwhite population dynamics and resource selection during the breeding and non-breeding season in southwest Missouri, USA using data from adult and juvenile bobwhite fitted with radio-transmitters. Land cover of our study sites ranged from large blocks of native grasslands maintained with prescribed fire and grazing to more traditional management resulting in small patches of grasslands interspersed with food plots, disked idle areas, and woody cover. During the breeding season, relative probability of selection by broods increased in relation to proportion of native grass managed by grazing and burning and proportion of cropland. Brood survival was also greatest on native grasslands burned and grazed within the past 2 growing seasons. During the fall and winter, relative probability of selection by adults increased as woody edge density increased. Fall and winter survival increased as distance from trees increased and decreased as distance to shrubs increased. Our integrated population model indicated that the number of young hatched per female and adult breeding season survival were greatest on sites with the most native grassland managed by prescribed fire with grazing. However, non-breeding season survival was greater on sites with more agriculture or food plots and woody cover. Abundance declined across all sites from 2016 to 2019. Our work suggests that native grasslands managed by prescribed fire with grazing can provide quail habitat superior to traditional management that strived for a mixture of agriculture, woody cover, and grassland. The combination of conservation grazing and fire in native grasslands interspersed with shrubs may provide the greatest chance for bobwhite populations to persist in southwest Missouri and similar landscapes.
Keywords: Colinus virginianus; full annual cycle; habitat management; grazing; integrated population model; native grasslands; prescribed fire; resource selection; survival